The Effect of Coach Gender on Competitive Weightlifting Performance for Men and Women Weightlifters - Mire, Abigail; Heintz, Elizabeth C.; Foreman, Jeremy J. (Frontiers in Sociology, 2021)
Gender of coaches relative to their athletes has recently garnered substantial attention in the public, the media, and academia. Relative to sports engulfed in controversy pertaining to men athletes being coached by women, such as professional baseball, basketball, and football, it is more common to see women coach men in competitive weightlifting, though only a small percent of men weightlifters are coached by women. In competitive weightlifting, coaches are responsible for both physically and mentally training athletes, and with the social barriers faced by women in a sport traditionally perceived as masculine, there may be mental training or communication benefits to training with a coach of a certain gender. Examining the gender of competitive weightlifters and their coaches, total weight lifted in the snatch and clean and jerk events are analyzed using OLS regression. Results indicate that men weightlifters perform better with men coaches. Women weightlifters perform better with men coaches until the age of 43, then they perform better with women coaches. The difference in performance may be due to several factors including historical bias against women in the sport.